Leadership in Action : Issues and Observations--Learning a Lesson in Executive Selection - Hogan, Robert (Center for Creative Leadership, 2008)
Top leaders are typically brought in to address one or two burning organizational needs; long-term success is sacrificed for the sake of short-term fixes.